Impact of Outdoor Environment to the Quality of Life - Eusuf, Muhammad Abu; Mohit, Mohammad Abdul; Sami Eusuf, MMR; Ibrahim, Mansor (Elsevier, 2014)
The features of outdoor environment in urban spaces and morphology affect the quality of life (QoL) of urban inhabitants and visitors. The purpose of this study is to develop an extensive hypothesis on the parametric valuation related to the modification of the urban environment and inhabitant’s QoL by systematic literature review, field observation and proposal on an alternative design strategy. The parameters include microclimatic variations, urban space and traffic, waste minimization and other influencing factors are desired to contemplate for rigorous investigation. Factors play a key role on the adaptation of QoL and responsively affect the dwellers attitude and behaviour.